Numerical simulation of landfill aeration using computational fluid dynamics - Fytanidis, Dimitrios K.; Voudrias, Evangelos A. (Waste management (Elmsford), 2014)
•Use of Computational Fluid Dynamics for the simulation of landfill aeration systems.•Results are in good agreement with previous investigations.•An oxygen-based zone of influence around a well is larger than a pressure-based.•A hybrid pressure aeration system is more effective than a constant pressure one. The present study is an application of Computational Fluid Dynamics (CFD) to the numerical simulation of landfill aeration systems. Specifically, the CFD algorithms provided by the commercial solver ANSYS Fluent 14.0, combined with an in-house source code developed to modify the main solver, were used. The unsaturated multiphase flow of air and liquid phases and the biochemical processes for aerobic biodegradation of the organic fraction of municipal solid waste were simulated taking into consideration their temporal and spatial evolution, as well as complex effects, such as oxygen mass transfer across phases, unsaturated flow effects (capillary suction and unsaturated hydraulic conductivity), temperature variations due to biochemical processes and environmental correction factors for the applied kinetics (Monod and 1st order kinetics). The developed model results were compared with literature experimental data. Also, pilot scale simulations and sensitivity analysis were implemented. Moreover, simulation results of a hypothetical single aeration well were shown, while its zone of influence was estimated using both the pressure and oxygen distribution. Finally, a case study was simulated for a hypothetical landfill aeration system. Both a static (steadily positive or negative relative pressure with time) and a hybrid (following a square wave pattern of positive and negative values of relative pressure with time) scenarios for the aeration wells were examined. The results showed that the present model is capable of simulating landfill aeration and the obtained results were in good agreement with corresponding previous experimental and numerical investigations.